Oxford Handbook of Obstetrics and Gynaecology - Collins, Sally (Obstetrics specialist); Arulkumaran, Sabaratnam (Oxford medical publications., 2008)
It's finally here: the brand new edition of this bestselling handbook of obstetrics and gynaecology! The new author team, combining both UK trainees and highly experienced obstetricians and gynaecologists, have put together a wealth of practical advice on diagnosing and managing common problems and emergencies. Key evidence-based guidelines are supported by internet references, providing the most up-to-date clinical information as well as the perfect starting point for preparationfor postgraduate exams. With its fresh layout, new content, and high quality illustrations, this is the must-have Ox.